2016
DOI: 10.4025/actascianimsci.v38i3.31377
|View full text |Cite
|
Sign up to set email alerts
|

<b>Genetic analysis of fertility traits of Holstein dairy cattle in warm and temperate climate

Abstract: ABSTRACT. The edited data set for the estimation of heritability, genetic and phenotypic correlations of fertility traits contained up to 23,402 records from 10,894 cows calved between 2001 and 2015. Heritability estimates for success in first service (FS), gestation length (GL), number of inseminations (NI), insemination outcome (IO), calving interval (CI), calving birth weight (CBW) and days open (DO) were low and ranged between 0.016 (DO) and 0.123 (GL). Repeatability of fertility traits was estimated to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
4
22
3
Order By: Relevance
“…However, it is higher than the means reported for the same breed in other countries (Salem et al, (2006), Rahbar et al, (2016), Chawala et al, (2017) and Brzakova et al, (2019).…”
Section: Resultscontrasting
confidence: 60%
See 3 more Smart Citations
“…However, it is higher than the means reported for the same breed in other countries (Salem et al, (2006), Rahbar et al, (2016), Chawala et al, (2017) and Brzakova et al, (2019).…”
Section: Resultscontrasting
confidence: 60%
“…Studies conducted in Egypt reported a higher mean of LTMY of 26935kg, 21796kg and 18309kg, respectively by Abou-Bakr, 2009, Oudah et al, (2013) and Salem and Hammoud (2019), respectively. However, smaller means were 6970kg and 8831kg reported by Khattab et al, (2009) and Rahbar et al, (2016), respectively. In this study, the coefficient of variation (CV %) for productive traits (table 2) ranged from 37.05 to 68.74. and were 25.21 and 99.93 for fertility traits (CI and DO), respectively.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Javed, Abdullah, Akhtar, and Afzal () reported a similar correlation between calving interval and first lactation milk yield (0.46 ± 0.46) for Sahiwal cattle. Rahbar, Aminafshar, Abdullahpour, and Chamani () reported significant and positive correlation of calving interval with days open. The lower heritability estimate (14%) of calving interval suggested a relatively smaller contribution of genetic factors to this trait.…”
Section: Resultsmentioning
confidence: 98%